Applying Entrepreneurship to the Arts How Artists, Creatives, and Performers Can Use Startup Principles to Build Careers and Generate Income. - Landry, Paula (Milton : Productivity Press, 2022)
This book puts successful startup tools in the hands of creators: performers, artists, entertainers, creatives, and media makers seeking to launch like a business and generate more income. Readers will learn essential entrepreneurial principles taught to founders in the startup community. Creatives who read this book will learn: How to launch their creative startups Ways to run and market their venture efficiently Effective methods to test new services, products, and experiences To incorporate their entire skill set in an authentic way That they can do all of this now, without business classes or special training With actionable information, real-world case studies as examples, and specific steps to build business acumen from an artistic perspective, this book puts entrepreneurial tools into the frameworks and mindsets of those working in creative fields. Paula Landry, MBA, is a creator, writer/filmmaker, and musician who has been teaching and coaching creatives for a decade, through undergraduate and graduate programs in New York City, as well as atvarious non-profits.
Plan -- Bulid and test -- Create with constraints -- Share with awareness -- Generate and launch -- Manage and analyze.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Arts -- Management; Cultural industries -- Management; Entrepreneurship; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Home-Based Businesses